Integrating Thematic Tafsir of Qur’an Surah Al-‘Alaq with Local Wisdom-Based Learning Media: An Islamic Education Model for Generation Z in West Sumatra - Alif Utama, Mohamad Maulidin (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2025)
Efforts to develop Islamic learning media that integrate Qur’anic values with local wisdom remain limited, even though Generation Z-as digital natives, and the main users of digital tool- still requires approaches that are relevant to both culturally grounded and religiously relevant. This study examines the philosophy of Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS-SBK) as a framework for aligning local wisdom with Qur’anic values, particularly through the utilization of Qur’anic verses in character building. The research seeks to evaluate the effectiveness of digital learning media, identify the implementation challenges, propose an integration model of the tafseer of Quran surah Al-‘Alaq with ABS-SBK, and analyze its implications for Islamic learning among Generation Z. A qualitative case study was conducted using an in-depth interviews, classroom observations, and documentation. The findings reveal that integrating the tafsir of QS. Al-‘Alaq with the ABS-SBK philosophy fosters student engagement, supports contextualized learning, and reinforces the Minangkabau Islamic cultural identity. Challenges include infrastructure limitations, educators’ technological skills, and content validation processes. The proposed model combines thematic tafsir with ABS-SBK-based multimedia content, enhanced through gamification and digital storytelling. This study highlights the importance of collaboration among scholars, educators, and technology developers in designing innovative and value-based Islamic learning media for Generation Z.